New ischnacanthiform jaw bones from the Lower Devonian of Podolia, Ukraine - Victor Voichyshyn; Hubert Szaniawski (Acta Palaeontologica Polonica, 2018)
Investigation of fish fauna assemblages obtained by dissolution of calcareous rock samples from Early Devonian marine deposits of Podolia revealed new material of ischnacanthiform jaw bones. One family Podoliacanthidae fam. nov. and two new genera and species, Drygantacanthus semirotunda gen. et sp. nov. and Kasperacanthus serratus gen. et sp. nov., are established. The new family is based on one main key feature, the presence of denticle groups of Podoliacanthus type situated on the lingual tooth row. The family comprises three genera, Podoliacanthus, Drygantacanthus gen. nov., and Kasperacanthus gen. nov., as well as one new form undetermined to generic level. Another new form described in open nomenclature displays the remains of the most powerful known jaws among Podolian ischnacanthids known to now. The new forms have diverse main teeth morphology, which probably reflect differentiated hunting methods.